The Relevance of Communication Skills to Islamic Educational Leadership - Muhammad Thohri; Siti Aminah; Muhammad Muhammad (Electronic Journal of Education, Social Economics and Technology, 2025)
Leadership communication in Islamic education is a key aspect of managing educational institutions to ensure the teaching and learning process aligns with their vision and mission. Effective communication can enhance motivation, performance, and work control, while ineffective communication may hinder the institution's goal achievement.  This study aims to explore the communication skills of leaders in managing, educating, guiding, and directing Islamic educational institutions, as well as strategies to improve communication effectiveness in the learning process. The research adopts a library research method, gathering data from books, journals, and related scientific articles. The analysis is conducted qualitatively and descriptively, examining leadership communication patterns and their impact on institutional performance.  The results show that effective communication between leaders and institutional members is crucial for improving collaboration and motivation. Conversely, poor communication can obstruct the attainment of the institution's vision and mission.  In conclusion, effective communication in Islamic educational leadership is vital for institutional success. Leaders with strong communication skills can enhance the motivation and performance of members, enabling the achievement of educational goals. As an implication, communication training for educational leaders should be implemented to improve institutional performance